Assessing Change in Physician Practice Organization Profile in South Carolina: A Longitudinal Study. Issue 3 (15th April 2019) - Breneman, Charity B.; Probst, Janice C.; Crouch, Elizabeth; Eberth, Jan M.
Abstract: Background: Physician practice organization is shifting away from solo, independent practices toward direct employment, but trends for rural‐urban differences are often analyzed by dichotomizing rurality. The purpose of this analysis was to examine trends in practice organization across 3 levels of rurality over a 21‐year period in South Carolina. Methods: Physician license renewal forms were used to ascertain type of practice organization where physicians worked in South Carolina between 1995 and 2015. Physicians were divided into 4 categories: physicians in independent solo practices, physicians in independent group practices, employed physicians, and other. Historical trends in type of practice organization were evaluated for each level of rurality (metropolitan, micropolitan, and small adjacent/remote rural) using the National Cancer Institute's Joinpoint regression models. Results: There was a continual increase in physician renewals indicating employment, with an average annual increase of 5.9%. Micropolitan rural counties demonstrated the greatest average increase in license renewals for employed physicians (average annual increase = 7.4%; P < .05). The ratio of license renewals per 100, 000 population for physicians in independent solo practices declined significantly over time. Micropolitan and small adjacent/remote rural counties saw an increase in the annual decline for this type of practice organization in 2007. Conclusions: A shift toward physician employment was observed at all levels of rurality. Rural counties exhibited a more pronounced transition between the types of practice organization compared to metropolitan counties. Research is needed to address the implications of these changes for rural providers and patients.